2020
DOI: 10.1029/2020wr028140
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Acoustic Sensing as a Distributed Hydraulic Sensor in Fractured Bedrock

Abstract: Distributed acoustic sensing (DAS) was originally intended to measure oscillatory strain at frequencies of 1 Hz or more on a fiber optic cable. Recently, measurements at much lower frequencies have opened the possibility of using DAS as a dynamic strain sensor in boreholes. A fiber optic cable mechanically coupled to a geologic formation will strain in response to hydraulic stresses in pores and fractures. A DAS interrogator can measure dynamic strain in the borehole, which can be related to fluid pressure thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Becker et al. (2020) showed that distributed sensing with fiber optics can probe nano strain oscillations across flowing fractures along a borehole drilled through a fracture network, thus opening avenues to identify such flowing fractures in a fractured reservoir. Z. Zhang et al.…”
Section: Field Observations and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Becker et al. (2020) showed that distributed sensing with fiber optics can probe nano strain oscillations across flowing fractures along a borehole drilled through a fracture network, thus opening avenues to identify such flowing fractures in a fractured reservoir. Z. Zhang et al.…”
Section: Field Observations and Experimentsmentioning
confidence: 99%
“…Thermo-Hydro-Mechanical Interactions Within a Fracture Network Becker et al (2020) showed that distributed sensing with fiber optics can probe nano strain oscillations across flowing fractures along a borehole drilled through a fracture network, thus opening avenues to identify such flowing fractures in a fractured reservoir. Z. used coupled forward hydro-mechanical modeling to show how low-frequency DAS and DSS signals can inform interactions between flowing and non-flowing fractures within a fracture network.…”
Section: Distributed Fiber Optic Sensing Enabled High-resolution Prob...mentioning
confidence: 99%
“…Also, it is well known that for FIMT type of installations, the gel filling allows for a creep and differential movement of fibers with respect to its surroundings which makes strain sensing unreliable for greater deformations and longer periods (e.g. Lipus et al, 2018, Becker et al, 2020. However, a creep over many meters or even kilometers is most likely improbable.…”
Section: Assessment Of Measuring Errorsmentioning
confidence: 99%
“…Optical fibers are able to carry light and propagate it over long distances with minimum attenuation, and so is a preferred medium for broad-band transmission systems around the world. When using the scattering properties of the glass fibers, the fiber can be turned into a distributed sensing system that provides substantial advantages over conventional electronic sensors [ 1 , 2 , 3 , 4 ]. Optical fiber sensors are able to measure external environment variables (e.g., temperature and strain; [ 5 ]) along their length with fine spatial intervals.…”
Section: Introductionmentioning
confidence: 99%